STRATEGI PENGELOLAAN INSTAGRAM @TAMANWISATAPUNCAK_OFFICIAL DALAM PRODUKSI KONTEN INFORMASI (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study addresses the issue of "What are the account manager's strategies for producing informational content on the @tamanwisatapuncak_official Instagram account?" The objectives of this study are: 1) To determine the efforts of the @tamanwisatapuncak_official Account Manager in producing informational content, and 2) To identify the obstacles faced by the @tamanwisatapuncak_official Instagram account manager in producing informational content. This research is classified as descriptive qualitative, using a communication science approach. The primary data sources for this study are the account manager, editor, and director. Secondary data sources include books and the internet. Furthermore, the data collection methods used are observation, interviews, and documentation. Data processing and analysis techniques are then carried out in three stages: data reduction, data presentation, and conclusion drawing. The results of this study indicate that 1) the efforts of the @tamanwisatapuncak_official Instagram account manager in producing informational content include: Pre-production stages consist of determining the concept and content idea, planning the location and shooting time, and preparing production equipment. 2) The production stages include efforts to capture videos and images on location. 3) The post-production stages consist of editing, revising, and publishing. 2) The obstacles faced by the @tamanwisatapuncak_official Instagram account manager in producing informational content include unstable network, lack of production team (human resources), lack of content equipment, and visitors' refusal to be photographed. Research implications: 1) Theoretical implications: contributing to the development of digital communication studies, particularly in the context of informational content production strategies on social media. 2) Practical implications: serving as a reference for social media account managers, particularly in the tourism sector, in designing and implementing effective content production strategies. Furthermore, understanding technical constraints and limited resources can assist account managers in devising appropriate solutions. Additionally, understanding technical constraints and limited resources can help Account Management design solutions, such as HR training, planned production scheduling, and optimization of available editing and content tools.